A fundamental investigation into the microwave assisted leaching of sulphide minerals - Al-Harahsheh, Mohammad (2005)
Microwave assisted leaching has been investigated in an attempt to improve both the yield of extracted metal and reduce processing time. This is especially pertinent in view of the increased demands for metal and more environmentally friendly processes.